Patients with Primary Malignant Retroperitoneal Tumor: Surgical Treatment Outcomes - D. V. Omelchenko; A. B. Vasin (Креативная хирургия и онкология)
Introduction. Determining the most optimal tactics for the diagnosis and treatment of primary malignant retroperitoneal tumors is highly relevant today. This can be attributed to a number of reasons, including: lack of versatile approach to the treatment of primary malignant retroperitoneal tumors, lack of effective ways to prevent the disease progression, small number of publications on this issue. All this motivates oncologists engaged in the treatment of patients with this pathology to accumulate and analyze the results of treatment of each patient. Materials and methods. The study was based on data analysis of 32 patients with primary retroperitoneal tumors, 26 of which were treated at the Yaroslavl Clinical Oncological Hospital from 2016 to 2021 with the diagnosis of primary malignant retroperitoneal tumors. Results and discussion. 13 patients out of 26 (50%) had T4N0M0. Stage 3B was detected in 73.08% of patients. Histologically verified: liposarcoma — 19.23%, leiomyosarcoma and myxoid liposarcoma — 15.38% each, the remaining formations comprised 3.8% each and consisted to different types of sarcomas from mesodermal rudiments. 22 patients (84.62%) had high-grade tumors, 4 patients (15.38%) had low-grade tumors. 22 patients underwent radical surgical treatment. Isolated resection of the tumor was performed in 11 patients (50%), and 11 operations (50%) were accompanied by combined or concurrent tumor resection. No postoperative complications were reported. Histologically confirmed tumor invasion was detected in 50% of operated patients. The most frequently involved organ was the kidney. Conclusion. The obtained data indicate high resectability rates for tumors of this localization. Analysis of the excised tumor volume revealed direct correlation with the degree of tumor malignancy. High rates of one-, three- and five-year survival of patients testify to the effectiveness of radical surgical resection both in case of isolated resection and combined or concurrent resection. However, frequent recurrences and, therefore, repeated surgical interventions lead to a regressive reduction in survival.